Implementando la instrucción diferenciada en el aula de clase de idioma extranjero - Marriott Toledo, Heidi Marlen (2018)
Currently, English learning is more necessary than ever before. However, teachers often face mixed skills clases, with different English levels, which generates the need to apply proactive methodologies geared to tackle all this diversity while learning. This is how Differentiated Instruction (DI) in foreign language influences the teaching process allowing the teacher to integrate in the teaching learning process informed instructional decisions in the different ways of learning, learning styles, and individual differences in order to apply adequate activities for every student. The objective of this research is to provide the theorethical framework that confirm that the application of DI in the language classroom can solve the problems of heterogeneity in English classes. To achieve this, first, the theorethical background will be provided to identify similarities that determine good practices for this model. After that, a descriptive analysis will provide information about the diverse configuration of students who can benefit from DI, and finally, the differentiated application of this model in a specific skill will be presented according to the standards for English instruction in Ecuador.